Omental torsion mimicking acute apendicitis. Case report and literature review - Manrique-Sila, Fátima (2024)
Torsion of the greater omentum (TE) is a rare cause of acute abdominal pain, with nonspecific symptoms that frequently mimic acute appendicitis. We present the case of a 44-year-old woman with symptoms compatible with acute appendicitis. She underwent laparoscopy, revealing the greater omentum adhered to the anterior wall of the abdomen, devitalized, twisted on its own axis, which was resolved with laparoscopic omentectomy and complementary appendectomy. ET is potentially serious, requiring urgent treatment. Tomographic study is useful, but most are diagnosed intraoperatively. Therefore, it should be included in the differential diagnosis of acute abdomen. The definitive treatment is surgical, with laparoscopic omentectomy being the choice. Although there is conservative treatment if it is previously diagnosed through radiology.